Pendampingan Aktifitas Senam Kaki bagi Peserta Prolanis Diabetes Melitus di Wilayah Kerja Puskesmas Kujangsari Kota Bandung: Active Leg Exercise Support for Prolanis Diabetes Mellitus Participants in the Kujangsari Health Center Area, City of Bandung - Nugraha, Nandang Jamiat; Humnah, Habibah; Triearti, Charlita (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Prediabetic individuals participating in the Prediabetes Lifestyle Program (prolanis DM) have exhibited irregular adherence to lower limb exercises, resulting in persistent fluctuations in blood glucose levels. Engaging in lower limb exercises holds substantial benefits for stabilizing blood glucose levels in individuals with diabetes mellitus (DM). This community nursing intervention aims to enhance the ability of prediabetic prolanis participants to perform lower limb exercises. The intervention involves direct assistance and guidance to prediabetic prolanis participants during their lower limb exercise routines. A total of 31 participants were provided with instructional videos on DM-specific lower limb exercises and were evaluated twice over two months during their visits to the Kujangsari Primary Health Center. After the sessions, the lower limb exercises were assessed using a scoring format ranging from 1 to 3, with final results categorized accordingly. Results indicated that 54.8% of participants achieved a 'Good' rating for their lower limb exercise performance. This personalized support and guidance are anticipated to augment the participants' lower limb exercise proficiency and motivation to exercise regularly. The DM-specific lower limb exercise videos are envisioned to serve as a reference for participants, enabling them to pursue self-care by performing these exercises at home and maintaining stable blood glucose levels.